Strengthening the performance of MSMEs in North Sumatra based on social impact with government support as mediation - Kurniawan, Benni; Sihombing, Marlon; Nasution, Muhammad Arifin; Ridho, Hatta (Research Journal in Advanced Humanities, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving economic growth, job creation, and poverty reduction in North Sumatra Province. However, optimizing MSME performance still faces various structural challenges, particularly related to the social impact generated by MSMEs, such as job creation and improving community welfare, which have not fully contributed to improving MSME performance. This indicates a gap in the process of transforming social impact into business performance. Government support through policies, financing, and assistance is expected to bridge this gap, but its effectiveness as a mediation mechanism still shows mixed results. The lack of studies that simultaneously integrate social impact, government support, and MSME performance confirms a research gap regarding the strategic role of government support in strengthening the influence of social impact on MSME performance. This study aims to analyze the influence of social impact on optimizing MSME performance, with government support as a mediating variable, among small business actors in North Sumatra. A quantitative approach was used with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method to test the causal relationships between variables simultaneously. The results showed that social impact and government support had a positive and significant effect on optimizing MSME performance. This was also the case when government support was used as a mediating variable between social impact and performance. Government support plays an important role as a mediating mechanism in strengthening the influence of social impact-oriented business activities on MSME performance. The findings of this study contribute theoretically by enriching the literature on development economics and social impact-based entrepreneurship, as well as contributing practically to local governments in formulating more adaptive, inclusive, and public value-oriented MSME assistance programs.